Migration and the rural-urban continuum: evidence from the rural Philippines - Quisumbing, Agnes R.; McNiven, Scott (International Food Policy Research Institute, 2005)
Using a unique longitudinal data set to follow movements across generations, this study explores the nature of the migration experience for rural dwellers in the Philippines. The paper asks the following questions: (1) Do destinations—more rural and more urban areas and places in-between—attract different types of people? (2) Do migrants move for different reasons? (3) Do migration-support networks, job search strategies, and occupational profiles differ?